2015
DOI: 10.1039/c5cp01689d
|View full text |Cite
|
Sign up to set email alerts
|

Exciton intrachain transport induced by interchain packing configurations in conjugated polymers

Abstract: Based on a tight binding model combined with a nonadiabatic dynamics approach, we theoretically investigate the exciton intrachain transport in conjugated polymers with different interchain packing configurations. We construct two different interchain packing configurations, i.e. linear and exponential forms, and simulate the dynamical processes of the exciton transport in these systems. We find that, in both cases, there exists a distribution of driving force for exciton transport, which stems from the gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Meng and coauthors found that the driving force for intrachain exciton transport is smoother for linear than for exponential interchain packing so the exciton cannot move in the latter case when it is photogenerated far away from the neighboring chain. 415 4.6.2. Control of the Exciton Energy Transfer by Conformational Changes.…”
Section: Chemicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Meng and coauthors found that the driving force for intrachain exciton transport is smoother for linear than for exponential interchain packing so the exciton cannot move in the latter case when it is photogenerated far away from the neighboring chain. 415 4.6.2. Control of the Exciton Energy Transfer by Conformational Changes.…”
Section: Chemicalmentioning
confidence: 99%
“…Meng et al considered two different forms of interchain packing configurations, namely, linear and exponential interchain packing configurations (Figure ), for which the dynamical processes for the exciton intrachain transport were theoretically simulated. Meng and coauthors found that the driving force for intrachain exciton transport is smoother for linear than for exponential interchain packing so the exciton cannot move in the latter case when it is photogenerated far away from the neighboring chain …”
Section: Transport Of Excitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the nuclear motions can evolve on multiple potential energy surfaces in the dynamic processes, which guarantees the nonadiabatic nature of the quantum dynamics approach used in our simulations. Here, eqs and can be numerically solved by the Runge–Kutta method of order eight with step-size control, which has been widely used and proven to be an effective approach in the study of dynamic processes in polymers. , Values of the model parameters are set according to those generally used for cis -polyacetylene, that is, t 0 = 2.5 eV, α = 41 eV/nm, K = 2100 eV/nm 2 , M = 13.5 × 10 5 eV·fs 2 /nm 2 , a = 0.122 nm, and t e = 0.05 eV. Despite that the model is built for a specific polymer, the obtained results are expected to be qualitatively valid for other conjugated polymers.…”
Section: Theorymentioning
confidence: 99%
“…As we know, strongly bound electron–hole pairs (i.e., Frenkel excitons) can be generated in polymers right after photon absorption due to the presence of strong electron–lattice (e–l) interactions and low dielectric constant in these materials. , To realize efficient charge separation, prototypical PSCs are usually employed on the basis of bulk heterojunction (BHJ) architectures, in which polymers are used as electron-donor (D) and fullerene derivatives (or other small molecules) as electron-acceptor (A), respectively. In such systems, charge separation requires that the initially generated excitons can arrive at the D/A interfaces via different migration processes, which usually needs a time scale exceeding 1 ps due to the speed limitation of exciton migration . During this process, the large binding energy of excitons is generally considered to be overcome by a positive energetic offset between the lowest unoccupied molecular orbitals (or the highest occupied molecular orbitals) of the donor and acceptor, although some recent research studies have suggested that the energetic offset is not an important criterion for efficient charge separation. , …”
Section: Introductionmentioning
confidence: 99%